Impact Of Digital Technology In Higher Education (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Digital technologies are now embedded in our society. Focus has  shifted from whether or not to use them in teaching and learning,  to understanding which technologies can be used for what specific  educational purposes and then to investigate how best they can be  used and embedded across the range of educational contexts in  schools. The new digital technologies have permeated economy  markets, politics, our workplaces, the ways we communicate  with each other, our home activities, as well as operation of all  levels of education from kindergarten to doctoral studies. The new  technologies challenge higher education institutions worldwide  to redefine their student constituencies, their partners and  competitors and to redesign their research infrastructures and  teaching practices. The focus of this paper is to examine the role  of Information and Communication Technology|(ICT) in higher  education in India. the emergence of ICT has fundamentally  changed the practices of not only business and governance but  education as well. While the world is moving rapidly towards  digital media.The role of ICT in education has become increasingly  important. There has been an unprecedented growth in the use of  ICTs in teaching, research and extension activities. The sudden  boom in information Technology has transformed the way how  knowledge is disseminated today. One of the changes it has  brought about is the way how teachers interact and communicate  with the students and vice-versa.
Keywords: ICT; knowledge; Higher Education